Analisis Kesetimbangan Massa Dan Rendemen Pada Sistem Distilasi Daun Nilam Menjadi Minyak Atsiri - Mukhtar, Muharnif; Lubis, Riadini Wanty; ., Suherman; Mariono, Nanang Pat Sumantri (Fakultas Teknik UMSU, 2023)
Indonesia is one of the largest essential oil producing countries in the world and is supported by natural resources with climatic conditions, soil and plant species that are very suitable for the growth of patchouli plants. The use of essential oils today is not only as a raw material for fragrances and cosmetics but also in the health sector. One of the basic ingredients for producing essential oils is patchouli. The main thing that needs to be considered in the processing of this essential patchouli oil is the yield it produces. This study aims to analyze the mass balance and yield in the processing of patchouli essential oil in a distillation system with 5kg, 4kg, 3kg patchouli leaf raw material variations. Distillation of patchouli leaves was carried out using the steam and water distillation method with a temperature in the kettle not exceeding 100 oC for 6 hours. The main variables in the processing of patchouli leaves into essential oil are distillation efficiency and the yield obtained. The more mass of patchouli leaves used, the more it will increase the distillation efficiency of 79.7%, 82.1% and 82.4% as well as the yield of the resulting oil increased 1.67%, 1.7% and 1.78%